NANOG and LIN28 dramatically improve human cell reprogramming by modulating LIN41 and canonical WNT activities - Wang, Ling; Su, Yue; Huang, Chang; Yin, Yexuan; Chu, Alexander; Knupp, Alec; Tang, Young (Biology open, 2019)
Human cell reprogramming remains extremely inefficient and the underlying mechanisms by different reprogramming factors are elusive. We found that NANOG and LIN28 (NL) synergize to improve OCT4, SOX2, KLF4 and MYC (OSKM)-mediated reprogramming by ∼76-fold and shorten reprogramming latency by at least 1 week. This synergy is inhibited by GLIS1 but reinforced by an inhibitor of the histone methyltransferase DOT1L (iDOT1L) to a ∼127-fold increase in TRA-1-60-positive (+) iPSC colonies. Mechanistically, NL serve as the main drivers of reprogramming in cell epithelialization, the expression of Let-7 miRNA target LIN41, and the activation of canonical WNT/β-CATENIN signaling, which can be further enhanced by iDOT1L treatment. LIN41 overexpression in addition to OSKM similarly promoted cell epithelialization and WNT activation in reprogramming, and a dominant-negative LIN41 mutation significantly blocked NL- and iDOT1L-enhanced reprogramming. We also found that NL- and iDOT1L-induced canonical WNT activation facilitates the initial development kinetics of iPSCs. However, a substantial increase in more mature, homogeneous TRA-1-60+ colony formation was achieved by inhibiting WNT activity at the middle-to-late-reprogramming stage. We further found that LIN41 can replace LIN28 to synergize with NANOG, and that the coexpression of LIN41 with NL further enhanced the formation of mature iPSCs under WNT inhibition. Our study established LIN41 and canonical WNT signaling as the key downstream effectors of NL for the dramatic improvement in reprogramming efficiency and kinetics, and optimized a condition for the robust formation of mature human iPSC colonies from primary cells. This article has an associated First Person interview with the first author of the paper.